Implementasi Algoritma Naive Bayes Untuk Menentukan Lokasi Strategis Dalam Membuka Usaha Menengah Ke Bawah di Kota Medan (Studi Kasus: Disperindag Kota Medan) - Samuel Suprianto (Universitas Budi Darma, 2020)
The business can be influenced by the location of the location and the type of business that was built in the specified location and can develop over time but it is not impossible for bankruptcy to occur because the type of business is not in the right location and promising due to factors that do not support at that location, include that area where the population is not too dense and the land is not that large. For this reason, the authors conduct research on strategic locations to open a particular type of business depending on the location found by the Naive Bayes method. Where the method is used to predict accurately from the many locations that have been researched after that it is determined which is more appropriate area.